Pre-Sleep Recital Application for Android System - Sahani, Muhamad Syariffudin; Sari, Suhaila; Md Taujuddin, Nik Shahidah Afifi; Roslan, Hazli; Ibrahim, Nabilah (Evolution in Electrical and Electronic Engineering, 2023)
Islam advices us to pray and recite the dhikrs and prayers before sleep. The mobile phone can be utilized to spread and improve awareness of Islamic practices. There are various types of application related to the recital of Islamic prayers available, but it is difficult to find an application that provides a brief but comprehensive combination of prayers and dhikrs before sleep. This project provides audio and visual content with a display, audio play in the background, and sleep timer mode. The software to develop the application development is implemented using the Visual Studio Code (VSC), and the framework of the application using the Flutter. The mobile application is Islamic Before Sleep Recital. It can be accessed from the Google Play Store under the name “Islamic Before Sleep Recital” application. The majority of respondents said that it is good (62.5%), and 37.5% said that the application is very good in terms of user friendliness. After using the applications, 31.3% respondents said that their sleep quality are very good, and 56.3% claimed their sleep quality are good. In conclusion, most respondents agreed that their sleep quality have improved. Furthermore, all respondents are satisfied in terms of the user-friendliness of this application.